Strategi Pemko Medan Dalam Mempertahankan Istana Maimun sebagai Ikon Wisata Kota Medan - Fadilah, Nurhikmah; Saritza, Zahra; Aulia, Fadlan; Anwar, M. Fachri; Simamora, Irma Yusriani (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The tourist icon is one of the signs that characterizes a particular area. Each region must have its own tourist icon. One of them is the city of Medan, which has a tourit icon, the Maimoon Palace or what is commonly called the Deli Sultanate Palace. Is one of the icons of the country. To find out the strathey of Pemko Medan in mainting the Maimun palace, researchers used qualitative methodes with a socio-cultural approach. The method used is in- depth interviews and documentation. From the results of the interview the strstegy adopted by Pemko Medan is to continue to promote the Maimoon Palace on various social media, or major events helid im the city of Medan. From the Maimoon palace self, ot major events held ini the city of Medan. From the Maimoon Palace itserlf , it is to. Maintain comfot and cleanliess at the Maimun Palace itself. Keywords: strategy, maimoon palace, travel icon